One‐Step Synthesis of 2, 5‐Diaminoimidazoles and Total Synthesis of Methylglyoxal‐Derived Imidazolium Crosslink (MODIC). (12th November 2019) - Sabbasani, Venkata R.; Wang, Kung‐Pern; Streeter, Matthew D.; Spiegel, David A.
Abstract: Here we describe a general method for the synthesis of 2, 5‐diaminoimidazoles, which involves a thermal reaction between α‐aminoketones and substituted guanylhydrazines without the need for additives. As one of the few known ways to access the 2, 5‐diaminoimidazole motif, our method greatly expands the number of reported diaminoimidazoles and further supports our previous observations that these compounds spontaneously adopt the non‐aromatic 4( H ) tautomer. The reaction works successfully on both cyclic and acyclic amino ketone starting materials, as well as a range of substituted guanylhydrazines. Following optimization, the method was applied to the efficient synthesis of the advanced glycation end product (AGE) methylglyoxal‐derived imidazolium crosslink (MODIC). We expect that this method will enable rapid access to a variety of biologically important 2, 5‐diaminoimidazole‐containing products. Abstract : Eins mit allem : Eine allgemeine Methode zur Synthese von 2, 5‐Diaminoimidazolen durch die thermische Reaktion von α‐Aminoketonen mit substituierten Guanylhydrazinen wurde entwickelt. Die einstufige Reaktion funktioniert mit cyclischen und acyclischen Aminoketon‐Startmaterialien sowie einer Reihe substituierter Guanylhydrazine. Sie wurde in der Synthese des „Advanced Glycation Endproduct" (AGE) „Methylglyoxal‐Derived Imidazolium Crosslink" (MODIC) eingesetzt.